139k views
2 votes
Multiply and subtract these polynomials and simplify. Enter your response in standard form. (2x^3 − 3x + 11) − (3x^2 + 1)(4 − 8x)

User Immy
by
5.7k points

2 Answers

3 votes

Answer:

=26x^3−12x^2+5x+7

Explanation:

2x^3−3x+11−(3x^2+1)(4−8x)

Distribute:

=2x^3+−3x+11+24x^3+−12x^2+8x+−4

Combine Like Terms:

=2x^3+−3x+11+24x^3+−12x2+8x+−4

=(2x^3+24x^3)+(−12x^2)+(−3x+8x)+(11+−4)

=26x^3+−12x^2+5x+7

User Eswari
by
4.4k points
7 votes

Answer:

From the question you gave me, I got the answer from simplifying it.

My answer is:

26x^3 - 12x^2 + 5x + 7

Please let me know if you need any more assistance!

User Justin Wignall
by
5.5k points